2017
DOI: 10.1007/s00227-017-3258-y
|View full text |Cite
|
Sign up to set email alerts
|

Multiple paternity in a Pacific marine turtle population: maternal attributes, offspring outcomes and demographic inferences

Abstract: Multiple paternity in loggerhead turtles Manuscript Click here to download Manuscript MABI-D-17-00403 revised_clean.docx Click here to view linked References

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 95 publications
(120 reference statements)
0
3
0
Order By: Relevance
“…Our comparison of within-clutch morphological variation between multiple and single paternity clut -ches supports the idea that multiple paternity may not be beneficial to female turtles or their offspring. Similarly, Howe et al (2018) found that multiple paternity did not significantly influence loggerhead turtle hatchling size or within-clutch size variation. Previous studies on frogs (Crinia georgiana; Byrne & Roberts 2000) and wild house mice (Mus musculus; Thonhauser et al 2014) also found that multiple paternity did not increase variation in offspring size.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Our comparison of within-clutch morphological variation between multiple and single paternity clut -ches supports the idea that multiple paternity may not be beneficial to female turtles or their offspring. Similarly, Howe et al (2018) found that multiple paternity did not significantly influence loggerhead turtle hatchling size or within-clutch size variation. Previous studies on frogs (Crinia georgiana; Byrne & Roberts 2000) and wild house mice (Mus musculus; Thonhauser et al 2014) also found that multiple paternity did not increase variation in offspring size.…”
Section: Discussionmentioning
confidence: 90%
“…This technique is useful as it allows researchers to assess the quantity and quality of males' offspring without direct observation of mating. To date, there have been few published studies to apply multiple paternity analysis in this way (Lee & Hays 2004, Stewart & Dutton 2014, Alfaro-Núñez et al 2015, Howe et al 2018.…”
Section: Discussionmentioning
confidence: 99%
“…Satellite tracking and direct observations showed that breeding usually occurs before the beginning of the nesting season and all the clutches laid within a season are usually sired by the same fathers (Hays et al, 2022). However, sperm storage across multiple seasons has not been formally demonstrated in marine turtles, as opposed to terrestrial and freshwater turtles (Owens, 1980;Whitaker, 2006), but several studies have suggested that it is likely (Howe et al, 2017;Theissinger et al, 2009;Wright et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies of marine turtles have found little evidence for this (e.g. Zbinden et al 2007, Wright et al 2013, Alfaro-Núñez et al 2015; but see Phillips et al 2017, Howe et al 2018, although it is possible for such effects to exist but be almost undetectable, if they can recover fitness that might otherwise be lost (e.g. Price et al 2010, Michalczyk et al 2011.…”
Section: Introductionmentioning
confidence: 99%